Pharmacometabolomics of Meglumine Antimoniate in Patients With Cutaneous Leishmaniasis - Vargas, Deninson Alejandro; Prieto, Miguel Dario; Martínez-Valencia, Alvaro José; Cossio, Alexandra; Burgess, Karl E. V.; Burchmore, Richard J.S.; Gómez, María Adelaida (Frontiers in Pharmacology, 2019)
Control of cutaneous leishmaniasis (CL) in the Americas is dependent on chemotherapy with parenteral pentavalent antimonials. High rates of treatment failure urge the search for predictive and prognostic markers of therapeutic responsiveness. In this study we aimed to identify biomarkers of therapeutic response during treatment with meglumine antimoniate (MA).We conducted untargeted metabolomic profiling of plasma samples from CL patients (n=39; 25 who cured and 14 who did not cure), obtained before and at the end of treatment. Exposure to MA induced metabolic perturbations primarily reflecting alteration in long-chain fatty acid β-oxidation and energy production. Allantoin, N-acetylglutamine, taurine and pyruvate were significantly more abundant in samples from patients who responded to treatment, and were predictive and prognostic of treatment outcome in this patient cohort (AUC>0.7). In an ex vivo model of infection, allantoin but not taurine enhanced the MA-dependent killing of intracellular Leishmania (Viannia) panamensis. Our results support the participation of metabolites mediating antioxidant and wound healing responses in clinical cure of CL, revealing relationships between metabolism and immune responses in the outcome of antileishmanial treatment.